2001
DOI: 10.1108/00346650110366964
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nutrition knowledge on eating behavior – the role of grade level

Abstract: Eating behaviors of children and adolescents are important in establishing adults’ preferences and behaviors. Nutrition knowledge is one of the factors that could influence an adolescent’s eating behavior. Therefore the relationship between nutrition knowledge and eating behaviors of adolescents was examined in this research project. The participants were students from a middle school in Ohio. The students were asked to answer a questionnaire CANKAP (Comprehensive Assessment of Nutrition Knowledge, Attitudes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
1
10
1
2
Order By: Relevance
“…These findings support similar research by Brown et al. 14 and Pizouznia 20 in the apparent lack of vegetable consumption among young consumers, which also emphasizes the continued gap between theory and practice with regard to healthy eating.…”
Section: Discussionsupporting
confidence: 89%
“…These findings support similar research by Brown et al. 14 and Pizouznia 20 in the apparent lack of vegetable consumption among young consumers, which also emphasizes the continued gap between theory and practice with regard to healthy eating.…”
Section: Discussionsupporting
confidence: 89%
“…The statistical tests did not reveal any significant relationships between the respondents' age and their knowledge of food, attitudes about food, dietary behaviour and the likelihood to achieve a balanced diet. This contradicted some previous theory and findings, such as Pirouznia's (2001), that older students had a greater ability to translate their nutritional knowledge into eating behaviour than younger students, which suggested that the older respondents would have had higher levels of knowledge of food and be more likely to achieve a balanced diet. In addition, the finding that there was no relationship between the respondents' age and their attitudes about food contradicts the assertion by Brown et al.…”
Section: Resultscontrasting
confidence: 95%
“…Although the theory that knowledge can translate into behaviour has been studied and positive relationships have been identified (Saegert and Young, 1983; Read et al. , 1988; Pirouznia, 2001; Hamilton‐Ekeke and Thomas, 2007), it has also been recognized that adolescents' eating behaviour will not always reflect their level of knowledge (Axelson et al. , 1985; Story and Resnick, 1986; Shepherd and Stockley, 1987; Shepherd and Towler, 1992; Stafleu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Reported results on eating behaviour and its relation to nutrition knowledge are, however, inconsistent (Steenhuis et al, 1996;Pirouznia, 2001). One of the reasons suggested for the inconsistency is that the nutrition knowledge could have been poorly assessed (Kristal et al, 1990;Parmenter & Wardle, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…An institution based food product development project was initiated to determine the sensory acceptability of bakery products with increased fibre contents due to the belief that fibre has a negative impact on taste (Colavito et al, 1996). As part of this project, the fibre knowledge of the target population of young adults, represented by higher education students, had to be determined as nutrition knowledge is a factor linked to eating behaviour (Steenhuis et al, 1996;Pirouznia, 2001) that may influence product acceptability.…”
Section: Introductionmentioning
confidence: 99%